STUDY OF THE THERMO-PHYSICAL PROPERTIES OF POLYPROPYLENE/GRANITE PARTICULATES COMPOSITES AS DENTAL IMPLANTS - Abdulwahab, M.; Mojisola, T.; Lawal, H. A. (FUDMA JOURNAL OF SCIENCES, 2025)
This study focuses on the development of a composite material for potential dental applications by investigating the influence of granite particulate (GTP) loading on the physical properties of polypropylene (PP) matrix. This was achieved by washing the granite in distilled water, followed by drying and then ball milling for 72 hours. Subsequently, the powdered granite was combined with polypropylene (PP) in a two-roll mill compounder at a temperature of 150°C for 5 minutes. Five distinct samples with varying GTP percentages ranging from 10% to 50 wt. % were produced. The samples were thereafter subjected to testing for various physical properties such as density, thermal conductivity and diffusivity, specific heat capacity etc. Standard analytical techniques such as DSC and TGA were employed to analyze the sample. It was observed from the obtained results that sample containing 50 wt. % PP/GTP demonstrates enhanced properties of such as thermal degradation resistance of 75.23 % as compared to 94 % weight loss of the other tested weight ratios, thereby making it a choice candidate for potential applications in dentistry.
Keywords: Polypropylene (PP); Granite particulate (GTP); Physical properties; Dental Implants; Dentistry